The effectiveness of exercise for the prevention and treatment of antenatal depression: systematic review with meta‐analysis. (17th June 2014) - Daley, AJ; Foster, L; Long, G; Palmer, C; Robinson, O; Walmsley, H; Ward, R
<x xml:space="preserve">Abstract</x> Background Antenatal depression can have harmful consequences for the mother and fetus. Exercise may be a useful intervention to prevent and treat antenatal depression. Objectives This systematic review aims to establish whether there is sufficient evidence to conclude that exercise is an effective intervention for preventing and treating antenatal depression. Search strategy Searches using electronic databases from MEDLINE, Cochrane Library, CINAHL, EMBASE, AMED and PsycINFO were performed. Selection criteria Randomised controlled trials (RCT) that compared any type of exercise intervention with any comparator in pregnant women were eligible for inclusion. Data collection and analysis Meta‐analysis was performed calculating standardised mean differences (SMD). Main results Six trials (seven comparisons) were eligible for inclusion. Meta‐analysis showed a significant reduction in depression scores (SMD −0.46, 95% CI −0.87 to −0.05, P = 0.03, I2 = 68%) for exercise interventions relative to comparator groups. The test for subgroup differences in women who were non‐depressed (one trial) (SMD −0.74, 95%CI −1.22 to −0.27, P = 0.002) and depressed (five trials) (SMD −0.41, 95% CI −0.88 to 0.07, P = 0.09) at baseline was not significant (P = 0.32). The test for subgroup differences between aerobic (one trial) and non‐aerobic exercise (five trials) was also nonsignificant (P = 0.32). Authors' conclusions We found some evidence that exercise may be effective in treating depression during pregnancy but this conclusion is based on a small number of low‐moderate quality trials with significant heterogeneity and wide confidence intervals.